1973
DOI: 10.1039/dt9730001468
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of ferrocenyl ketones and acids in dimethyl sulphoxide and related solvents

Abstract: Compounds of the type FcCOAr, FcCOR (R = Alkyl), and FcCHO undergo photoaquation (A > 280 nm) in wet dimethyl sulphoxide, pyridine, dimethylformamide, and related solvents to give a cyclopentadienyliron salt of the acid ArC0,H or RC0,H together with a molecule of free cyclopentadiene derived from the originally substituted ring. At shorter wavelengths in DMSO a secondary reaction gives rise to the intense purple colouration described previously. Ferrocenecarboxylic acid undergoes similar consecutive changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 0 publications
3
18
0
Order By: Relevance
“…[38,39] This is because metal phosphonates normally form poorly crystalline compounds and the ferrocene moiety is sensitive to oxygen, water, heat, and light when it is attached with electron-withdrawing substituents on the cyclopentadienyl (Cp) rings. [40][41][42] Until now, only Henderson et al have reported platinum-ferrocenylphosphonate complexes and studied their antitumor activity [39] and Bideau et al have reported a zinc(ii)-ferrocenylphosphonate polymer with a unique 2D ferrocene arrangement anchored on a 1D Zn-O-P-O-Zn backbone. [38] To the best of our knowledge, metalferrocenylphosphonate cage complexes have not been reported.…”
Section: H T U N G T R E N N U N G (Fmpa) 4 a C H T U N G T R E N Nmentioning
confidence: 98%
“…[38,39] This is because metal phosphonates normally form poorly crystalline compounds and the ferrocene moiety is sensitive to oxygen, water, heat, and light when it is attached with electron-withdrawing substituents on the cyclopentadienyl (Cp) rings. [40][41][42] Until now, only Henderson et al have reported platinum-ferrocenylphosphonate complexes and studied their antitumor activity [39] and Bideau et al have reported a zinc(ii)-ferrocenylphosphonate polymer with a unique 2D ferrocene arrangement anchored on a 1D Zn-O-P-O-Zn backbone. [38] To the best of our knowledge, metalferrocenylphosphonate cage complexes have not been reported.…”
Section: H T U N G T R E N N U N G (Fmpa) 4 a C H T U N G T R E N Nmentioning
confidence: 98%
“…It has been reported that electron-withdrawing substituent on the cyclopentadienyl ring for ferrocene derivatives may provide a greater photolability, and can undergo photolysis in some solvents to cause both ringmetal and ring-carbonyl cleavages, giving Fe 2þ cation and some free radicals [34][35][36][37][38]. If the mixture of metal ions, 2,2 0 -bpy, 1,1 0 -ferrocenedicarboxylic acid and NaOH in methanol-water solution are under light, it could turn from orange to dark-brown solution and then produce brown precipitate, whose composition cannot be identified, compounds (1)-(4) could not be obtained.…”
Section: Synthesismentioning
confidence: 99%
“…All calculations were done with SHELX-97 [19]. Further details are given in Ferrocene derivatives bearing electron-withdrawing groups undergo photolysis in some solvents to cause cleavage of both ring-metal and ring-carbonyl, giving free Fe 2þ cation and free radicals [20][21][22][23]. Thus, all procedures should be performed in the dark.…”
Section: X-ray Measurementsmentioning
confidence: 99%